Hydrogen-oxidizing electron transport components in nitrogen-fixing Azotobacter vinelandii. - Wong, T Y (1984)
Membranes from N2-fixing Azotobacter vinelandii were isolated to identify electron transport components involved in H2 oxidation. We found direct evidence for the involvement of cytochromes b, c, and d in H2 oxidation by the use of H2-reduced minus O2-oxidized absorption difference spectra. Carbon monoxide spectra showed that H2 reduced cytochrome d but not cytochrome o. Inhibition of H2 oxidation by cyanide was monophasic with a high Ki (135 microM); this was attributed to cytochrome d. Cyanide inhibition of malate oxidation showed the presence of an additional, low Ki (0.1 microM cyanide) component in the membranes; this was attributed to cytochrome o. However, H2 oxidation was not sensitive to this cyanide concentration. Chlorpromazine (at 160 microM) markedly inhibited malate oxidation, but it did not greatly inhibit H2 oxidation. Irradiation of membranes with UV light inhibited H2 oxidation. Adding A. vinelandii Q8 to the UV-damaged membranes partially restored H2 oxidation activity, whereas addition of UV-treated Q8 did not increase the activity. 2-n-Heptyl-4-hydroxyquinoline-N-oxide inhibited both H2 and malate oxidation.